Understanding Diatom Cell Wall Silicification—Moving Forward - Hildebrand, Mark; Lerch, Sarah J. L.; Shrestha, Roshan P. (Frontiers in Marine Science, 2018)
The silicified cell walls of diatoms have inspired the interest of researchers for several centuries, and our understanding of their properties and formation has developed in synch with the development of observational and analytical techniques. Over the past 20 years, approaches used to characterize the molecular components involved in cell wall silicification have evolved, and this has provided significant insights into fundamental aspects of silicification, and promises to continue to do so. Diatom cell wall formation is highly dynamic but, apart from microscopic investigations, most previous molecular characterizations have been on completely formed structures, and thus only provide information on a static end point in the process. However, recent studies that monitor when components are made, and how they are transported to the silica deposition vesicle (SDV), indicate that investigation into the true dynamics of the process is possible. Real-time imaging and genetic manipulation offer the promise of elucidating the spatio-temporal dynamics of, and interactions between, components, which will be essential to understand how structure formation is controlled and coordinated. This review is aimed at describing the approaches that have been used to characterize diatom silicification, integrating newer concepts based on results from diverse approaches, and raising questions that still need to be addressed, leveraging the diverse tools and techniques we now have.